The Effect of Heat Events on Prehospital and Retrieval Service Utilization in Rural and Remote Areas: A Scoping Review. Issue 6 (2nd December 2021) - O'Donnell, Elen; Honan, Bridget; Quilty, Simon; Schultz, Rebecca
Abstract: Introduction: It is well-established that heatwaves increase demand for emergency transport in metropolitan areas; however, little is known about the impact of heat events on demand for prehospital retrieval services in rural and remote areas, or how heatwaves are defined in this context. Inclusion Criteria: Papers were eligible for inclusion if they reported on the impact of a heat event on the activity of a prehospital and retrieval service in a rural or remote area. Methods: A search of PubMed, Cochrane, Science Direct, CINAHL, and Google Scholar databases was undertaken on August 18, 2020 using search terms related to emergency medical transport, extreme heat, and rural or remote. Data relevant to the impact of heat on retrieval service activity were extracted, as well as definitions of extreme heat. Results: Two papers were identified, both from Australia. Both found that heat events increased the number of road ambulance call-outs. Both studies used the Excess Heat Factor (EHF) to define heatwave periods of interest. Conclusions: This review found almost no primary literature on demand for prehospital retrieval services in rural and remote areas, and no data specifically related to aeromedical transport. The research did recognize the disproportionate impact of heat-related increase in service demand on Australian rural and regional health services. With the effects of climate change already being felt, there is an urgent need for more research and action in this area.